2018
DOI: 10.1103/physrevb.98.035421
|View full text |Cite
|
Sign up to set email alerts
|

Collision-dominated conductance in clean two-dimensional metals

Abstract: We study the temperature-dependent corrections to the conductance due to electron-electron (ee) interactions in clean two-dimensional conductors, such as lightly doped graphene or other Dirac matter. We use semiclassical Boltzmann kinetic theory to solve the problem of collision-dominated transport between reflection-free contacts. Time-reversal symmetry and the kinematic constraints of scattering in two dimensions (2D) ensure that inversion-odd and inversion-even distortions of the quasiparticle distribution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…The corresponding current density is given by Eq. (12) with v µ , p ±µ , and Φ ±µ taken (20) and has the temperature dependence T 4 ln |E F /T |. A similar temperature dependence was recently obtained for the relaxation rate of higher-order odd angular harmonics of electron distribution in 2D systems with parabolic spectrum due to electron-electron collisions.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The corresponding current density is given by Eq. (12) with v µ , p ±µ , and Φ ±µ taken (20) and has the temperature dependence T 4 ln |E F /T |. A similar temperature dependence was recently obtained for the relaxation rate of higher-order odd angular harmonics of electron distribution in 2D systems with parabolic spectrum due to electron-electron collisions.…”
supporting
confidence: 71%
“…The T 4 dependence was predicted by Gurzhi et al 19 , and the additional logarithmic factor was recently found in Ref. 20 . The j(E F /E SO ) dependence is shown in Fig.…”
supporting
confidence: 53%
“…However, in reality, whenever the Fermi surface is a convex polygon, this assumption is likely to break down. The problem is most studied on circular (isotropic) Fermi surfaces [49][50][51][52],…”
Section: First-order Hydrodynamicsmentioning
confidence: 99%